The laws regulating affirmative action in the workplace and its impact on covid-19 pandemic - Skhosana, Zanele Mpho (My University, 2022)
The aim of this research is to determine the laws that regulate affirmative action in the workplace and the impact Covid-19 has on affirmative action. This research focuses on the history of affirmative action in South Africa and the United States of America. Both countries have a similar history of discrimination and racial segregation. The United States of America is one of the most progressive countries on the issue of affirmative action. The comparison of South Africa with the United States of America will enhance the applicability and effectiveness of affirmative action. Past discrimination is a huge contributing factor to the imbalances and inequalities experienced in the workplace. A measure in a form of affirmative action was established to redress past injustices, however, there are many controversies around the topic and its effectiveness. The Covid-19 pandemic has made matters worse in that many people have been laid off, resulting in the retrenchments and the regress of affirmative action and its purpose. The findings of this research conclude that Covid-19 has negatively affected the process of affirmative action. As such, employers during this trying time prefer only individuals who are fully qualified and experienced as the employees have been reduced. As long as affirmative action applies to individuals or a group of individuals with certain skin colour or sex regardless of their past privileges this racial tension might never be relieved. In order to effectively implement affirmative action, South Africa has to focus on the institutions that cause the problem rather than dealing with the final results
Thesis (LL.M. (Labour Law)) -- University of Limpopo, 2022
Keywords: Laws; Past discrimination; Inequalities; Workplace; COVID-19 (Disease); Affirmative action programs -- South Africa; Affirmative action programs -- Law and legislation -- United States; Affirmative action programs -- Law and legislation -- South Africa; Affirmative action programs -- United States; Discrimination in employment